Telling Global Public Health Stories: Narrative Message Design for Issues Management. (August 2016) - Barbour, Joshua B.; Doshi, Marissa J.; Hernández, Leandra H.
In consultation with the U.S. Centers for Disease Control and Prevention's Center for Global Health (CDC CGH), this study compared narrative and non-narrative message designs for global public health initiative issues management. A multiple-message experimental design prompted participants ( N = 669) to read a message about a CDC CGH initiative, and measured perceptions of agency reputation, support for a global public health mission, and intentions to share information. Narrative message design had direct effects on intentions to share the message interpersonally and through social media and indirect effects on the outcomes through perceptions of message features and mediating states (i.e., story structure, understanding, personal relevance, information overload) and transportation. The study contributes to theory and practice by confirming the mediating role of transportation, building on a message features approach to the study of narrative persuasion, and speaking to the challenges of issues management in global public health.